2015
DOI: 10.1086/679970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Share Remuneration System on Fisheries Management Targets and Rent Distribution

Abstract: A B S T R A C TMost fisheries worldwide remunerate their crew with a share system, where crew receive a part of the revenues or a part of the revenues less costs, rather than a fixed wage. Although labor is one of the main costs in fisheries and the share remuneration system has a strong influence on firm behavior and its economic performance, little attention has been paid it. In a share remuneration system, crew salaries can significantly increase when the economic performance of a vessel improves. This allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Macher, Guyader, Talidec, & Bertignac, 2008;Macher et al, 2013;Merzéréaud, Biais, Lissardy, Bertignac, & Biseau, 2013;Merzéréaud et al, 2011;Simmonds et al, 2011;Raveau et al, 2012;Guillén et al, 2013;Guillén, Macher, Merzéréaud, Fifas, & Guyader, 2014;Guillén, Macher, Merzéréaud, Boncoeur, & Guyader, 2015;EU STECF, 2015a,b,c. 15 SIMFISH Bartelings, Hamon, Berkenhagen, & Buisman, 2015Kempf et al, 2016.…”
Section: Stoch Hcr (Itq Wealth)mentioning
confidence: 99%
“…Macher, Guyader, Talidec, & Bertignac, 2008;Macher et al, 2013;Merzéréaud, Biais, Lissardy, Bertignac, & Biseau, 2013;Merzéréaud et al, 2011;Simmonds et al, 2011;Raveau et al, 2012;Guillén et al, 2013;Guillén, Macher, Merzéréaud, Fifas, & Guyader, 2014;Guillén, Macher, Merzéréaud, Boncoeur, & Guyader, 2015;EU STECF, 2015a,b,c. 15 SIMFISH Bartelings, Hamon, Berkenhagen, & Buisman, 2015Kempf et al, 2016.…”
Section: Stoch Hcr (Itq Wealth)mentioning
confidence: 99%
“…Similar results were obtained for the Bay of Biscay nephrops fishery where crew members receive a shared salary as in case 3. Guillen et al (2015) estimated that if In shared remuneration systems, labor costs are independent of the crew number, and consequently the average wage depends on the crew number. While in fixed remuneration systems, the average wage is fixed (constant), and so labor costs are proportional to the crew number.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the bioeconomic equilibrium is reached at a higher fishing effort level for the fixed remuneration. However, in Guillen et al, (2015), fixed remuneration was found to be more conservative, mainly as a result of the initial value given to the opportunity cost of labor:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations